2018
DOI: 10.14715/cmb/2017.64.15.12
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Leontice leontopetalum and Bongardia chrysogonum on oxidative stress and neuroprotection in PTZ kindling epilepsy in rats

Abstract: We investigated the effects of Leontice leontopetalum and Bongardia chrysogonum on apoptosis, gamma-aminobutyric acid (GABA A ) receptor positive cell number, cyclin-B1 and bcl-2 levels and oxidative stress in pentylenetetrazol (PTZ) kindling in rats. Kindling was produced by subconvulsant doses of PTZ treatments in rats. Wistar albino rats were divided into 4 groups; Control, PTZ treated (PTZ), PTZ+L. leontopetalum extract treated (PTZ+LLE) and PTZ+B. chrysogonum extract treated (PTZ+BCE) groups. Extracts wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Nonetheless, a study reported increased TOS and OSI values in parallel with elevated MDA levels in a rat model of pentetrazol-induced epilepsy. 44 Consistent with the literature, our findings showed high MDA, TOS and OSI levels in the epilepsy group.…”
Section: Discussionsupporting
confidence: 92%
“…Nonetheless, a study reported increased TOS and OSI values in parallel with elevated MDA levels in a rat model of pentetrazol-induced epilepsy. 44 Consistent with the literature, our findings showed high MDA, TOS and OSI levels in the epilepsy group.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, PTZ dissolved in sterile 0.9% saline (NaCl) was injected into the animals of PTZ, PTZ + OT, and PTZ + NP-OT groups intraperitoneally for every 48 h. Similar to PTZ groups, all Ctrl groups were only injected with sterile saline. 66 Video recordings were taken following 20 min of the PTZ injections for the observation of the animals' behavior. Recordings of the observation period were used to score the seizures of the animals using Racine's scale revised for PTZ-kindling rats.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Grading subconvulsive PTZ (Sigma-Aldrich, MO, Cat# P6500) doses, which were 35 mg/kg from first injections, 37.5 mg/kg from second injections, and 40 mg/kg from third injections, were given to all PTZ groups. Therefore, PTZ dissolved in sterile 0.9% saline (NaCl) was injected into the animals of PTZ, PTZ + OT, and PTZ + NP-OT groups intraperitoneally for every 48 h. Similar to PTZ groups, all Ctrl groups were only injected with sterile saline …”
Section: Methodsmentioning
confidence: 99%
“…Monoamines are the major neuromodulators that contribute to seizure susceptibility and comorbid psychiatric symptoms in epilepsy (Svob Strac et al, 2016). Alternations in central monoamines have been reported in animals (Ergul Erkec et al, 2018) and human epileptic brain (Avoli et al, 2005; Naffah-Mazzacoratti et al, 1996) and increased monoamines and metabolite levels in the cerebrospinal fluid (Szabó et al, 2015). The elevated levels of noradrenaline (NA), 5-hydroxytryptamine (5-HT), and dopamine (DA) metabolites during epilepsy may represent an epiphenomenon, rather than a concerted strategy of local or distal neurons to contain an epileptogenic focus (Kurian et al, 2011).…”
mentioning
confidence: 99%